2004
DOI: 10.1016/j.ehj.2004.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine in obstructive sleep apnoea

Abstract: Aims Whether increased homocysteine is one mechanism linking obstructive sleep apnoea (OSA) to cardiovascular abnormalities is unclear. We hypothesised that plasma homocysteine would be higher in OSA patients than in control subjects, would increase further during sleep, and decrease after treatment with continuous positive airway pressure (CPAP). Methods and ResultsFor study A, homocysteine was measured in 22 OSA patients and 20 controls first before sleep, then after 5 h of untreated OSA, and then in the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
3
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 27 publications
1
26
3
4
Order By: Relevance
“…Together these results suggest that increased homocysteine levels are associated with the occurrence of ischemic heart disease in OSA patients, but OSA alone does not appear to be an inducer of increased plasma homocysteine. More rigorous time course studies by Svatikova et al [64] also showed that having OSA per se did not change homocysteine levels, and CPAP treatment was not effective in lowering homocysteine in patients with OSA [65]. In contrast, Jordan et al [66] reported that 7 of 16 untreated OSA patients showed homocysteine levels > 11.7 μM, and that the level of homocysteine was effectively lowered by CPAP treatment.…”
Section: Evidence For Altered Homocysteine Levels In Osa Patientsmentioning
confidence: 98%
“…Together these results suggest that increased homocysteine levels are associated with the occurrence of ischemic heart disease in OSA patients, but OSA alone does not appear to be an inducer of increased plasma homocysteine. More rigorous time course studies by Svatikova et al [64] also showed that having OSA per se did not change homocysteine levels, and CPAP treatment was not effective in lowering homocysteine in patients with OSA [65]. In contrast, Jordan et al [66] reported that 7 of 16 untreated OSA patients showed homocysteine levels > 11.7 μM, and that the level of homocysteine was effectively lowered by CPAP treatment.…”
Section: Evidence For Altered Homocysteine Levels In Osa Patientsmentioning
confidence: 98%
“…It is oxidized in the plasma during hydrogen peroxide production to form free radicals which are toxic to endothelial cells. Due to the damaged endothelium, high homocysteine levels also limit NO production, and recent studies have shown that circulating NO levels are decreased in OSAS patients [3,4,6]. …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, homocysteine causes oxidative stress in the endothelium, and decreases NO levels and the production of antioxidants. Thus homocysteine may increase the extent of oxidative stress induced by hypoxia episodes in OSAS [3,4,6]. Normally endothelial cells detoxify homocysteine by releasing NO, which forms S-nitroso-homocysteine adducts by binding to homocysteine [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations